Surveying the POSNA Landscape: What Can We Learn From Society Survey Studies?. Issue 1 (January 2020) - Williams, Brendan A.; Guerrero, Andres; Blakemore, Laurel C.; Frick, Steven L.
Abstract : Background: A growing trend of survey-based research has been seen in the field of pediatric orthopaedics. The purpose of this study was to describe patterns of surveys of Pediatric Orthopaedic Society of North America (POSNA) membership and evaluate for associations between study characteristics and response rates in order to inform future research efforts. We hypothesized that studies with fewer survey questions and study group or committee involvement would demonstrate higher response rates. Methods: A systematic review of the literature was performed to identify all peer-reviewed survey publications targeting POSNA members published up to December 2017. Included studies were reviewed to identify author and publication characteristics, survey development and methodology, survey distribution procedures, and response rates. Statistical analyses were performed to describe publication patterns and evaluate for associations between study characteristics and response rates. Results: Thirty-four studies published from 1991 to 2017 were identified as meeting inclusion criteria, with a substantial increase noted over the last 3 years. Studies included 4.6 (SD 1.9) authors and 14.7% had affiliations with study groups or committees. Survey development methodology was detailed in only 1 study. Surveys included a median of 19.5 questions (3 to 108) and were primarily electronically distributed. The mean survey response rate was 42% with a downward trend noted over the studied time period. None of the studied author, publication, and design characteristics were associated with increased response rates. Conclusions: Survey-based studies of the POSNA membership have become increasingly popular study designs in recent years. Response rates are lower than reports in other physician cohorts, and appear to be declining, possibly representative of respondent fatigue. No associations were identified between response rates and the modifiable study characteristics evaluated (number of authors, committee or subgroup affiliation, number of questions, and mode of distribution). Efforts should be made to identify tactics to sustain participation as these studies become more widely utilized within our field. Optimizing study design and implementation features while valuing physician time and effort spent on survey completion is important to avoid member survey fatigue. Level of Evidence: Level V—systematic review of Level V research. Abstract : Supplemental Digital Content is available in the text.